Optimizing API Gateway Performance with Serverless Architectures: A Comprehensive Analysis - Sujeeth Reddy Pasham (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the optimization of API gateway performance through the implementation of serverless architectures. It delves into the fundamental concepts of serverless computing and its integration with API gateways, examining how this combination addresses key challenges in scalability, cost-efficiency, and security. The article discusses various strategies for performance optimization, including minimizing latency, implementing dynamic scaling, and reducing costs through efficient resource utilization. It also addresses critical security concerns and solutions specific to serverless environments. The article further explores the integration of cloud-native features and database strategies to enhance reliability and scalability. Through a series of real-world case studies, the article demonstrates the practical applications and benefits of serverless API gateways across different industries. While acknowledging the challenges and limitations of this approach, such as cold start issues and vendor lock-in concerns, the article also looks ahead to future developments in the field, including potential advancements in security, performance, and integration with emerging technologies like edge computing and 5G networks. Overall, this comprehensive article analysis provides valuable insights for developers, architects, and decision-makers looking to leverage serverless architectures for API management in modern, distributed applications.